Participação política, internet e competências infocomunicacionais: estudo com organizações da sociedade civil de Salvador - Lima, Jussara Borges de (2011)
ABSTRACT: The understanding of participation has been under pressure both by theoretical discussions, advocating the development of democracy by deepening participation, and by increasing deficiencies of government in meeting social needs. As a result, innovative participatory practices, which challenge established concepts, have been increasingly present in the work of civil society organizations. With the arrival of the internet and, with it, the potentiation of access to information and communication, its employment in democratic processes has been studied under several aspects. However, still few studies have investigated how, in fact, organizations use on-line resources for political participation. On the other hand, although these technologies provide a tool conducive to increased political participation, there are other factors that influence the phenomenon, as the skills to act and interact in cyberspace. Even though many authors agree that current work in cyberspace requires new skills, the discussion is still peripheral in the polls that mention them: do not clarify what would they be, their levels of quality and the relationship of these levels with different degrees of use of the internet. From this context, this thesis is guided by three goals: 1) to know the prevailing forms of political participation by civil society organizations in Salvador; 2) to raise what role the internet plays in the political activity of civil society organizations; 3) check which skills in digital environments are being used, developed and/or promoted by these organizations. The methodological procedures involved review of the literature on the themes that permeate the work, interviews with 44 civil society organizations in Salvador, direct observation in nine of them. The main results show that: (a) among the main forms of political participation are those aligned with deliberative democracy concepts; (b) there are changes in the way civil society organizations participate politically, mainly in the increment and variety they do that; (c) the main uses of the internet are related to maintaining constant contact with peers and also to search for information; (d) the Web has stimulated the renovation of some forms of political participation and the emergence of new; (e) competences can be organized in terms of operational competences, information competences and communication competences, being identified as a whole as infocommunication competences; (f) among the organizations surveyed, infocommunication competences are unevenly distributed, and communication competences are the least developed. We conclude that infocommunication competences tend to act in convergence with political competences, i.e, those with the motivation and knoledge necessary to participate and that dominate the skills to seize opportunities in digital environments have their actions enhanced.